MODERNITY, POST-STRUCTURALISM AND POSTMODERNISM IN THE INTERNATIONAL ADMINISTRATION THEORIES - Vargas-Hernández, José G. (Tourism & Management Studies, 2010)
The purpose of this paper is to analyzetheories of international managementcentered on modernity and postmodernityas an expression of correspondingorganizational theories. Starting from therationality of modern organization elements,it advances the organizational analysis inmore complex and uncertain environmentsin the context of economic globalizationprocesses which fi nally lead to profoundcultural transformations which affect thelocal managerial practices of organizationsoperating in the international realm. Ithas adopted a critical and inquiry positionof managerial theories based on westernepistemology which have sense in the nowestern context such as postmodernismwhich still is examining the rest of the worldin western terms.